2016
DOI: 10.1038/srep30942
|View full text |Cite
|
Sign up to set email alerts
|

Tomato yellow leaf curl virus: No evidence for replication in the insect vector Bemisia tabaci

Abstract: Begomovirus ssDNA plant virus (family Geminiviridae) replication within the Bemisia tabaci vector is controversial. Transovarial transmission, alteration to whitefly biology, or detection of viral transcripts in the vector are proposed as indirect evidence of replication of tomato yellow leaf curl virus (TYLCV). Recently, contrasting direct evidence has been reported regarding the capacity of TYLCV to replicate within individuals of B. tabaci based on quantitave PCR approaches. Time-course experiments to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In the second experiment [ 62 ], to prevent the acquisition of viral ssDNA and the dsDNA replicative form from plants that may stick to the capsid, B. tabaci B and Q were membrane-fed with DNAase I-treated purified TYLCV and TYLCV-Mld virions. Despite these precautions, both ssDNA and dsDNA were found associated with the particles.…”
Section: Organs Tissues and Cells Visited By Begomoviruses Circulmentioning
confidence: 99%
“…In the second experiment [ 62 ], to prevent the acquisition of viral ssDNA and the dsDNA replicative form from plants that may stick to the capsid, B. tabaci B and Q were membrane-fed with DNAase I-treated purified TYLCV and TYLCV-Mld virions. Despite these precautions, both ssDNA and dsDNA were found associated with the particles.…”
Section: Organs Tissues and Cells Visited By Begomoviruses Circulmentioning
confidence: 99%
“…Lifetime infectivity persistence, alterations to whitefly biology, and accumulation of viral DNA and transcripts in the vector have been proposed as evidence of replication of TYLCV in the whitefly vector ( 17 21 ). However, contrasting evidence has been reported by two studies, suggesting that TYLCV does not replicate within whiteflies ( 22 , 23 ). In these previous studies, time-course quantification of viral load using qPCR showed that TYLCV DNA loads within whole whiteflies remained stable or slightly decreased after viral acquisition had stopped.…”
Section: Discussionmentioning
confidence: 70%
“…A notable exception is tomato yellow leaf curl virus (TYLCV), one of the most devastating viral pathogens of tomato that has spread to more than 50 countries and regions ( 15 ). The possible replication of TYLCV in the whitefly vector has received considerable attention since 1994 ( 17 23 ). Whereas several studies provided evidence supporting replication of TYLCV in B. tabaci ( 17 21 ), other studies have reported that the virus does not replicate in the insect vector ( 22 , 23 ).…”
mentioning
confidence: 99%
“…tabaci in a persistent, circulative manner. Although kinetic quantification of the accumulation of both complementary and virion sense viral DNA molecules within B. tabaci using two step qPCR procedure showed no significant increase of viral DNA accumulation in the insect vector 30 , an increased amount of viral DNA corresponding to genes from both strands of TYLCV was detected by real-time RT-PCR in individuals of B. tabaci following 8 h of AAP on TYLCV-infected tomato plants or purified virions and then transferred to non TYLCV-host cotton plants 31 . Accumulation of viral DNA and viral transcripts was also observed using Fluorescence in situ hybridization analysis 31 .…”
Section: Discussionmentioning
confidence: 89%